Gratings: Light‐Driven Wide‐Range Nonmechanical Beam Steering and Spectrum Scanning Based on a Self‐Organized Liquid Crystal Grating Enabled by a Chiral Molecular Switch (Advanced Optical Materials 2/2015). Issue 2 (February 2015) - Jau, Hung‐Chang; Li, Yannian; Li, Cheng‐Chang; Chen, Chun‐Wei; Wang, Chun‐Ta; Bisoyi, Hari Krishna; Lin, Tsung‐Hsien; Bunning, Timothy J.; Li, Quan
<x xml:space="preserve">Abstract</x> A compact light‐driven beam‐steering device splits white light into a rainbow, enabling nonmechanical tuning of the diffraction angle. On page 166, it is fabricated by T.‐H. Lin, Q. Li, and co‐workers with a thin film of a self‐organized cholesteric liquid crystal grating containing a photosensitive chiral molecular switch. With the aid of the molecular switch, the grating period can vary reversibly in response to purple and green irradiation. The steering range tunability of around 30° boosts the applicability of such devices in light‐propagation control, spectroscopic applications, and beyond. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>